2012
DOI: 10.7745/kjssf.2012.45.4.582
|View full text |Cite
|
Sign up to set email alerts
|

Spore Associated Bacteria (SAB) of Arbuscular Mycorrhizal Fungi (AMF) and Plant Growth Promoting Rhizobacteria (PGPR) Increase Nutrient Uptake and Plant Growth Under Stress Conditions

Abstract: Microorganisms present in the rhizosphere soil plays a vital role in improving the plant growth and soil fertility. Many kinds of fertilizers including chemical and organic has been approached to improve the productivity. Though some of them showed significant improvement in yield, they failed to maintain the soil properties. Rather they negatively affected soil eventually, the land became unsuitable for agricultural. To overcome these problems, microorganisms have been used as effective alternative. For past … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 80 publications
(63 reference statements)
0
9
0
1
Order By: Relevance
“…This prophylactic activity of AMF is also endorsed to some root pathogen antagonists such as Trichoderma , Gliocladium , and PGPR like Pseudomonas and Bacillus (Kloepper et al 1991 ;Barea et al 1996 ). Growth-promoting bacteria and fungi work in collaboration with AMF by improvement in plant rooting, enhancement of plant growth and nutrition (Gopal et al 2012 ;, abiotic stress tolerance (Xun et al 2015 ), and biological control of pathogens; they also improve as well as facilitate symbiosis (Barea et al 1996 ). That means the presence of microbial community in soil rhizosphere or changes in rhizosphere enhances AMF-assisted antagonism to root pathogens.…”
Section: Microbial Community and Its Associations In Mycorrhizospherementioning
confidence: 99%
“…This prophylactic activity of AMF is also endorsed to some root pathogen antagonists such as Trichoderma , Gliocladium , and PGPR like Pseudomonas and Bacillus (Kloepper et al 1991 ;Barea et al 1996 ). Growth-promoting bacteria and fungi work in collaboration with AMF by improvement in plant rooting, enhancement of plant growth and nutrition (Gopal et al 2012 ;, abiotic stress tolerance (Xun et al 2015 ), and biological control of pathogens; they also improve as well as facilitate symbiosis (Barea et al 1996 ). That means the presence of microbial community in soil rhizosphere or changes in rhizosphere enhances AMF-assisted antagonism to root pathogens.…”
Section: Microbial Community and Its Associations In Mycorrhizospherementioning
confidence: 99%
“…Bacteria have been observed to live in close association with AMF (Gopal 2012), and have been isolated from different AMF spores (Xavier & Germida 2003;Roesti 2005;Horii & Ishii 2006;Cruz 2008;Bharadwaj 2008;, KSC_SF9c isolated from surface sterilized AMF spores . Xavier and Germida (2003) found 5 bacteria, , sp.…”
Section: Gigaspora In Vitromentioning
confidence: 99%
“…Certain Arbuscular Mycorrhizal Fungi hyphae produce hydrolytic enzymes which hydrolyses the biopolymers such as protein, chitin and cellulose that will help the AMF to degrade and infect the plant cell walls (Gopal . 2012).…”
Section: Amf Sporesmentioning
confidence: 99%
“…Even though plant cell membranes in trials treated with PGPRs, were found having less electron leakage, compared to control one treated irrigated with brackish water. In this tale, implicate PGPR in protection of plant cell membranes was possible by promoting the synthesis of lipids, that considered as structural constituents of most cellular membrane [14,15,16,17].…”
Section: Salt Accumulation In Plantmentioning
confidence: 99%